ANTIBACTERIAL ACTIVITY OF THREE PLANT EXTRACTS AGAINST MULTIDRUG RESISTANCE PSEUDOMONAS AERUGINOSA - Almawlah, Yassir Haider; Alaa, Hadeel; Al-jelawi, Sanaa O (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The increasing of antibiotic resistance of Pseudomonas aeruginosa causes serious worldwide infection problems. Hence, the objective of the study was to investigate the antibacterial activity of some plants against multidrug resistance P. aeruginosa isolated from burn-wound infections. Methods: About 30 burn-wound swab samples taken from hospitalized patients in Al-Hillah Teaching Hospital, Babylon Province. P. aeruginosaÂ isolates were isolated and identified depending on cultural, microbial, and biochemical characteristics. Then, the drug susceptibility was detected using different available antibiotics (8) to select multidrug resistance P. aeruginosa strains for using as test organisms. Three types of plants, including onion bulbs (Allium cepa), leaves of mint (Mentha asiatica), and outer peel of pomegranate (Punica granatum), were extracted by three types of solvent. The plant extracts were tested as antimicrobial substances. Results: About 9 samples were found positive by causing bacterial infection who presented invasive burn-wound infection from both sex and average age of 9 to 45 years. P. aeruginosa was found to be the most common isolates, 10 samples out of 30 samples. The most of multidrug resistanceÂ P. aeruginosa was used as test organisms to investigate the antimicrobial activity of three types of plant extracts. The plant extract of P. granatumÂ showed the highest antibacterial activity, followed by A. cepa, and finally, M. asiatica. Conclusion: From the study, all three studied plants had antibacterial activity against multidrug-resistant P. aeruginosa isolated from burn wound. It is a recommendation that natural products can use as therapeutic agents will probably not elicit resistance in bacteria. More research must continue to isolate and purify the active components and applied in experimental animal models. Â